The impact of atrial voltage and conduction velocity phenotypes on atrial fibrillation recurrence - Silva Cunha, Pedro (2024)
Publisher Copyright: 2024 Silva Cunha, Laranjo, Monteiro, Portugal, Guerra, Rocha, Pereira, Ferreira, Heijman and Oliveira.